Synthesis and HIV-1 integrase inhibitory activities of caffeoylglucosides - Kim, SN; Lee, JY; Kim, HJ; Shin, CG; Park, H; Lee, YS (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
Caffeoylglucosides, which have a glucose ring as a central linker, were synthesized from methyl D-glucosides, and their anti-HIV-1 activities were tested. Among them, four dicaffeoylglucosides (IC50 = 29.1-35.1 mu M), 6a, 6b, 9b and 10b, showed HIV-1 integrase inhibitory activity as potent as L-chicoric acid. (C) 2000 Elsevier Science Ltd. All rights reserved.